Pelatihan Internalisasi Kearifan Lokal untuk Meningkatkan Literasi Dasar - Putri, Kharisma Eka; Laila, Alfi; Mukmin, Bagus Amirul; Mujiwati , Endang Sri; Wiguna, Frans Aditia; Damariswara, Rian; Prastiya, Amadia; Nurkholidah, Manfia; Afandi, Syaiful (Dedikasi Nusantara: Jurnal Pengabdian Masyarakat Pendidikan Dasar, 2025)
Basic education is an important pillar in shaping students' character and literacy skills. In elementary schools in Kediri Regency and City, which are known for their rich culture and local wisdom, there are serious challenges in improving basic literacy among elementary school students. This training aims to internalize local wisdom in the basic education curriculum, with a focus on increasing the basic literacy of elementary school students. The implementation of this service is carried out through three stages, namely: planning, implementation and evaluation. From the training carried out, respondents gave positive attention to the training they attended. This was proven by 61.54% of participants answering strongly agreeing that training could increase teachers' understanding of basic literacy. And 73.08% of participants felt more confident in teaching after participating in the activity. This means that participants who previously lacked confidence in teaching, after participating in the training, became more confident in teaching. related to technology to understand. However, there are shortcomings in the implementation of training.